TRANSFORMASI BUDAYA HUKUM DALAM TRANSISI DARI OJEK KONVENSIONAL KE OJEK ONLINE - Wijaya, Eka; Indah, Kriscencia; Fernando, Yool (Ensiklopedia Sosial Review, 2025)
Abstract: This study explores the transformation of legal culture in the transition from conventional motorcycle taxis to digital app-based ride-hailing services in Indonesia. This shift not only reflects advancements in transportation technology but also indicates a change in compliance with legal norms and the governance of the informal transport sector. The research employs a normative legal method, focusing on the analysis of relevant regulations, legal principles, and academic literature. Conventional motorcycle taxis, which previously operated based on social norms and informal agreements, now face a more structured system through digital mechanisms, such as algorithm-based fare setting, driver rating systems, and platform-regulated services. This transformation requires the internalization of a new legal culture that prioritizes transparency, accountability, and consumer protection. Nevertheless, challenges arise, including conflicts of interest with conventional drivers, unequal legal literacy among drivers, and regulatory ambiguity. The study advocates for an adaptive, integrative, and participatory legal approach to ensure that this transformation is not merely technological but also reflects legal justice and inclusivity for all stakeholders in the online transport ecosystem.Keywords: legal culture, online motorcycle taxi, conventional motorcycle taxi, transportation law, normative approach, digitalization